Factors that contribute to the sales performance of product customization at Proseeska / Liyana Atiqah Abdul Rahman - Abdul Rahman, Liyana Atiqah (Faculty of Business and Management, 2008)
This research was conducted focusing on the 'sales performance' of product customization at Proseeska. Basically, it is difficult for Proseeska to stay survive within the industry since Proseeska which is one of the only few Bumiputera companies has to compete with many companies who offer the same services (customization) and majority owned by the Chinese businessman. Thus, to ensure the survival of the company and continuous growth in their sales performance, Proseeska need to find out what are the major factors that will help their products customization services become more effective so that they can enhance on it in the future. The main objective of this research is to study the significance and the level of relationship between factors which include supply chain effectiveness, product quality, retailer differentiation and salespeople's skills that can contribute to the sales performance of product customization at Proseeska. Besides that, this research will study about how far retailer differentiation factor become the major factor that contribute to their sales performance.